(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
This article presents the autline of the problems of quality management in an enterprise. The evolution of quality systems from quality control to currently implemented and used computer-aided systems had been analized. Examples of structures of such systems, as resources,personel, documentation, audit in the general approach had been given